Experimental infection on the locally isolated avian infectious laryngotracheitis virus: Zaid HaddamTaha1, Aida Bara Allawe1 and Khazzal Abbas Khazaal2 - Taha, Zaid Haddam (The Iraqi Journal of Veterinary Medicine, 2017)
The aim of this study was to evaluate virulence of local isolated avian infectious laryngotracheitis virus in experimentally infected chicken. Forty chickens 10 weeks old were used for the experimental infection with the locally isolated infectious laryngotracheitis virus. Chickens were divided into three groups, the first group consisted from 20 chickens infected with isolated infectious laryngotracheitis virus (2×104.16 TCID 50/50 µl) via eyes and mouth drops (one drop for each). The second group consisted of 10 chickens (non-infected) in contact with infected group inoculated with maintenance media (Minimum essential medium) on their eyes, to observe if the infected group can spread the virus. The third group consisted from 10 chickens (non-infected) were left as a control group separated from other groups, inoculated with maintenance media (Minimum essential medium) on their eyes. Clinical signs and mortality were examined daily up to 12 days post infection. The main clinical signs were depression coughing and gasping with mild conjunctivitis and no mortality. Enzyme linked immunosorbent assay (ELISA) test was conducted on the collected sera of chickens before and after experimental infection with isolated virus. The results of ELISA test was negative for all groups of chickens before experiment and positive results for infected group with titer approximately ranging from (2534-7910); Measure of central tendency and dispersion were used with mean (4874.75) and stander error (355.96\ 13.6%); while negative results for contact group and control group. Eighteen chickens (10 weeks old) separately were divided into three groups (infected, contact and control) treated as mention above and were used for histopathological examination; the chickens were killed, two in each group at 24 hr., 48 hr. and 72 hr. post infection. The histopathological changes on trachea and larynx were intracellur inclusion bodies formation detected at 72hr., post infection for infected group only.